Hubungan Dukungan Keluarga Dengan Kualitas Hidup Pasien Tuberkulosis Paru di Puskesmas Bangetayu Semarang - Alifah Dela Fahmawati; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Tuberculosis (TB) remains an infectious disease with a high incidence rate, transmitted through airborne droplets. TB patients often face discrimination in various aspects of life. This discrimination can worsen the treatment process, as they may avoid seeking treatment due to fear of being judged or ostracized. Family support for TB patients is expected to aid in treatment adherence and improve their quality of life. This study used a quantitative research design with a cross-sectional approach, involving 55 pulmonary TB patients at Bangetayu Public Health Center in Semarang, selected through total sampling. Data analysis was conducted using univariate and bivariate chi-square analysis. The univariate analysis revealed that 98.2% of respondents had good family support, and 89.1% had a fairly good quality of life. Bivariate analysis using the chi-square test showed a significant relationship between family support and the quality of life of pulmonary TB patients at Bangetayu Public Health Center, with a p-value of 0.001.